PERAN KELOMPOK TANI CITA IMBAYA TERHADAP PRODUKTIVITAS CABAI DI DESA RAANAN BARU KECAMATAN MOTOLING BARAT KABUPATEN MINAHASA SELATAN - Vicky M.E Karundeng; Tommy Ferdy Lolowang; Ellen G. Tangkere (Sam Ratulangi University, 2021)
This objective is to determine internal and external factors related to the productivity of chili farming and to find out the role of farmer groups in chili productivity in Raanan Baru village. This research was conducted from December 2019 to February 2020. Data collection methods were carried out by means of observation and questionnaires to farmer groups in Raanan Baru village which consisted of 30 members. In this study of chili farming, and to determine the factors related to the productivity of chili farming, seen from the crosstabulation test using SPSS v25 between each member characteristic (internal factors) and external factors with chili productivity, the descriptive method is used to determine the role of farmer groups on the productivity. Based on the results of research, internal and external factors related to the productivity of chili farming and the role of farmer groups on chili productivity. Factors related to farm productivity of members of the Cita Imbaya farmer group are age, level of education, farming status, intensity of exposure to counseling, and land tenure status. External factors for farmers in the form of business climate and business plan are also related to the productivity of members of the Cita Imbaya farmer group. The role of farmer groups that most members perceive is the role of farmer groups as a vehicle for cooperation and the role of farmer groups as farm production units.